2013
DOI: 10.1039/c3cp50854d
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism nano-imaging of two-dimensional chiral metal nanostructures

Abstract: Here we report on a nanoscale circular dichroism (CD) imaging for a two-dimensional chiral pair of nanostructures to elucidate the relationship between nanoscale chirality and CD activity. The chiral pair exhibited local ellipticity as high as 42 degrees in the CD signal at the center, with signals of both handedness coexisting in one nanostructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 21 publications
4
51
0
Order By: Relevance
“…In addition, the detection system may also distort the CD image, if the aperture of the near‐field probe had structural irregularity. However, it should be noted that similar centrosymmetric distribution of local CD for the S‐shaped structure was observed in our previous studies, with good reproducibility . Also, antisymmetric spatial distribution of local CD with respect to the central axis of the structure was obtained for an achiral 3/4‐arc structure similar to that in Figure b or Figure b .…”
Section: Resultssupporting
confidence: 87%
“…In addition, the detection system may also distort the CD image, if the aperture of the near‐field probe had structural irregularity. However, it should be noted that similar centrosymmetric distribution of local CD for the S‐shaped structure was observed in our previous studies, with good reproducibility . Also, antisymmetric spatial distribution of local CD with respect to the central axis of the structure was obtained for an achiral 3/4‐arc structure similar to that in Figure b or Figure b .…”
Section: Resultssupporting
confidence: 87%
“…[145][146][147] Prominent CD signals on the order of 10 -3 in absorbance units were observed in the macroscopic CD spectra of these samples measured with a propagating light, and the signs of the signals for "S" and mirrored "S" were mutually inverted. 146 Figure 17 shows near-field CD images of S-shaped and its mirrored counterpart gold nanostructures of the same sizes, and the profiles of the CD signals along the curves of the structures.…”
Section: Imaging Of Chiral and Achiral Gold Nanostructuresmentioning
confidence: 88%
“…Recently, we developed an apparatus with higher detection sensitivity of CD signals while maintaining a 100 nm (or higher) spatial resolution. [145][146][147][148] This design enabled a closer approach to the CD of metal nanostructures than has previously been made possible.…”
Section: Methods Of Near-field Measurements Of Local Optical Activitymentioning
confidence: 99%
“…The distribution of the local CD signals coming from chiral nanostructures explained the relation ship between chiroptical signal and nanoscale chirality. [91] A recent work showed that circularly polarized selective near field distribution explained the farfield chiral optical reac tions, in which several propagating waves in different direc tions were observed, and can analogize to nanoantennas (upper part of Figure 4b). [93] In this singlelayered structure which was in rosette geometry, it was believed that a signif icant magnetic mode was lost and thus caused weak chiral response.…”
Section: Quasi-2d Periodic Chiral Nanostructuresmentioning
confidence: 99%
“…[88] The interaction between periodic chiral metallic nanostructures and CPL, gives rise to interesting and unique chiral phenomena. [89][90][91] …”
Section: Periodic Chiral Nanostructuresmentioning
confidence: 99%